64 A Canadian multicentre survey of family needs when attending the pediatric emergency department. (21st October 2022) - Rahimi, Asa; Ali, Samina; Rajagopal, Manasi; Ma, Keon; Yaskina, Maryna; Goldman, Ran; Stang, Antonia; Beer, Darcy; Poonai, Naveen; Alqurashi, Waleed; Weingarten, Laura; Kam, April; et al.
Abstract: Background: Parents/caregivers strongly influence their child's experience in the pediatric emergency department (PED). Understanding their needs can improve families' PED experience and care. Objectives: To describe caregivers' perceived emotional, practical, and informational needs in the PED and how well these needs were met Design/Methods: This descriptive, cross-sectional survey with medical record review was conducted at 10 Canadian PEDs from October 2018 to March 2020, over a 1-week period every season, for a total of 4 weeks per site. Digital surveys available in English or French were completed by caregivers in the PED and 7 days after their visit. Health literacy was evaluated by the Newest Vital Sign tool. Results: A total of 2005 caregivers participated; mean age was 37.8 (SD 7.7) years, and 74.3% (1462/1969) were mothers. The mean child age was 5.9 (5.1) years and 51.9 % (1040/2003) were male. Caregivers' main spoken language was mostly English [72.6% (1425/1964)] or French [10.5% (206/1964)]. Over half of caregivers had a university/professional degree [51.0% (997/1956)]; 37.4% (746/1998) had possible/probable limited health literacy. 77.9% (1132/1454) of caregivers reported that their overall care needs were met. 71.7% (1081/1507) of caregivers reported that their emotional needs were met; they reported most emotional support by doctors [(35.6%, 535/1510)] and bedside nurses [(24.2%, 364/1507)]. The median (IQR) length of stay was 3.9 (2.6, 6.1) hours; 36.7% (546/1487) of caregivers felt they waited 'too long', and 77.8% (1158/1489) did not know how long they would have to wait. 11.7% of families were dissatisfied with the care updates provided. A safe PED was the top overall identified practical need [(45.1%, 602/1336)]. Internet access was the most important practical need throughout the visit [(28.1%, 378/1345)], while more space was the most reported [(49.8%, 696/1398)] need in the waiting room . The most desired improvements in the PED were better communication of wait times and delays [(41.1%, 745/1812)], shorter wait times [(38.8%, 699/1801)] and faster diagnosis [(24.9%, 449/1803)]. Conclusion: Almost one quarter of Canadian caregivers report that their overall needs were not fully met when attending the PED. Safety during the PED visit was of utmost importance. Nationally, caregivers value shorter wait times, rapid diagnosis, and better communication about perceived delays. Top practical needs included internet access and more waiting room space. Creating innovative waiting systems, better methods to share wait time information, free internet access, and improved physical spaces could better address identified caregiver needs in the PED.